2021
DOI: 10.1097/yco.0000000000000720
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the COVID-19 pandemic and lockdown on alcohol use disorders and complications

Abstract: Purpose of review To understand the effect of COVID-19 pandemic and lockdown on persons with alcohol use disorders. Recent findings From a total of 455 titles on COVID-19 and alcohol, 227 abstracts were screened, and 95 articles were reviewed (on November 25 th , 2020). The immediate effect was an increase in alcohol related emergencies including alcohol withdrawal, related suicides, and methanol toxicity. Although there are mixed findings wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
78
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 129 publications
5
78
1
2
Order By: Relevance
“…In contrast, some studies have found that an increase in consumption was associated with a lower initial consumption level [ 10 , 39 ]. In line with our findings, previous studies have also reported indications that heavy drinking has increased during the pandemic [ 18 , 38 ]. For instance, in England, the proportion of heavy drinkers (scoring 5+ on AUDIT-C) increased from 25% pre-pandemic to 38% during the April 2020 lockdown [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In contrast, some studies have found that an increase in consumption was associated with a lower initial consumption level [ 10 , 39 ]. In line with our findings, previous studies have also reported indications that heavy drinking has increased during the pandemic [ 18 , 38 ]. For instance, in England, the proportion of heavy drinkers (scoring 5+ on AUDIT-C) increased from 25% pre-pandemic to 38% during the April 2020 lockdown [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…Other studies have examined whether changes in alcohol consumption during the pandemic differed by initial consumption level. In addition to previous reports employing ESAC project data from Germany [ 22 ] and Norway [ 9 ], results from a number of studies employing other data sets and methods [ 21 , 36 , 37 , 38 ] corroborate our findings, showing that increased drinking was associated with higher initial consumption levels. In contrast, some studies have found that an increase in consumption was associated with a lower initial consumption level [ 10 , 39 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Alcohol and substances are being used during the pandemic as a way to cope with psychological distress concerning COVID-19 [ 24 ]. Recent studies reported that COVID-19 pandemic has had considerable impact that increased alcohol and substance use and related emergencies, and alcohol and drug users have difficulties in treatment access and adherence which can aggravate the ASUDs [ 25 28 ]. Our result showing the increase in the volume and the rate of ASUD-related PED visits within the 10-month period in 2020 was probably resulted from the increased use of the alcohol and drugs in general population in spite of the decreased capacity of the ASUD outpatient units as consistent with the literature.…”
Section: Discussionmentioning
confidence: 99%